Las tics como herramientas de interpretación del patrimonio natural del cantón Chilla provincia de El Oro - Ecuador - Guillen Pincay, Lili Vijaya; Ramirez Flores, Deyvis Dario (Machala : Universidad Técnica de Machala, 2023)
Natural Heritage Interpretation, a discipline aimed at creating meaningful connections between people and nature. Through an interdisciplinary approach, it examines how natural heritage interpretation promotes the appreciation, conservation, and understanding of the natural and cultural elements that shape our environment. Through a detailed analysis, it assesses how ICTs (Information and Communication Technologies) enrich the interpretation of natural heritage by enabling broader access to information, interactive experiences, and heightened environmental awareness. Various strategies and digital tools that facilitate information gathering, dissemination, and community participation in the preservation of this valuable heritage are explored. This research project aims to strengthen natural heritage through the use of ICTs, adopting an educational and participatory approach with the user, utilizing All Aperto museography to enhance the value of the heritage.
La Interpretación del Patrimonio Natural, una disciplina que busca crear vínculos significativos entre las personas y la naturaleza. A través de un enfoque interdisciplinario, se analiza cómo la interpretación del patrimonio natural promueve la apreciación, conservación y comprensión de los elementos naturales y culturales que conforman nuestro entorno. A través de un análisis detallado, se evalúa cómo las TICs enriquecen la interpretación del patrimonio natural al permitir un acceso más amplio a la información, una experiencia interactiva y una mayor conciencia ambiental. Se examinan diversas estrategias y herramientas digitales que permiten la recopilación, difusión de información, y participación de la comunidad en la conservación de este valioso patrimonio. Este proyecto de investigación tiene como objetivo fortalecer el patrimonio natural a través del uso de las TICS, desde un enfoque didáctico y participativo con el usuario utilizando la museografía All Aperto dando mayor valor al patrimonio.
Keywords: INTERPRETACION DEL PATRIMONIO; TICS; CONSERVACION; MUSEOGRAFIA ALL APERTO